High-resolution mapping of heterochromatin redistribution in a Drosophila position-effect variegation model. - Vogel, M.J.; Pagie, L.; Talhout, W.; Nieuwland, M.; Kerkhoven, R.M.; van Steensel, B. (Epigenetics & chromatin, 2009)
Position-effect variegation (PEV) is the stochastic transcriptional silencing of a gene positioned adjacent to heterochromatin. white-mottled X-chromosomal inversions in Drosophila are classic PEV models that show variegation of the eye color gene white due to its relocation next to pericentric heterochromatin. It has been suggested that in these models the spreading of heterochromatin across the rearrangement breakpoint causes the silencing of white. However, the extent of this spreading and the precise pattern of heterochromatin redistribution have remained unclear. To obtain insight into the mechanism of PEV, we constructed high-resolution binding maps of Heterochromatin Protein 1 (HP1) on white-mottled chromosomes.We find that HP1 invades euchromatin across the inversion breakpoints over approximately 175 kb and approximately 30 kb, causing de novo association of HP1 with 20 genes. However, HP1 binding levels in these regions show substantial local variation, and white is the most strongly bound gene. Remarkably, white is also the only gene that is detectably repressed by heterochromatin. Furthermore, we find that HP1 binding to the invaded region is particularly sensitive to the dosage of the histone methyltransferase Su(var)3-9, indicating that the de novo formed heterochromatin is less stable than naturally occurring constitutive heterochromatin.Our molecular maps demonstrate that heterochromatin can invade a normally euchromatic region, yet the strength of HP1 binding and effects on gene expression are highly dependent on local context. Our data suggest that the white gene has an unusual intrinsic affinity for heterochromatin, which may cause this gene to be more sensitive to PEV than most other genes.